3D-printed biphasic scaffolds for the simultaneous regeneration of osteochondral tissues. (29th July 2021) - Natarajan, Amrita BDS MTech; Sivadas, VP Ph.D; Nair, Prabha D Ph.D
Abstract: Osteochondral tissue engineering (OCTE) involves the simulation of highly complex tissues with disparate biomechanical properties. OCTE is regarded as the best option for treating osteochondral defects, most of the drawbacks of current treatment methodologies can be addressed by this method. In recent years, the conventional scaffolds used in cartilage and bone regeneration are gradually being replaced by 3D printed scaffolds (3DP). In the present study, we devised the strategy of 3D printing for fabricating biphasic and integrated scaffolds that are loaded with bioactive factors for enhancing the osteochondral tissue regeneration. Polycaprolactone (PCL) and poly(lactic-co-glycolic acid) (PLGA), is used along with bioactive factors (chondroitin sulphate and beta-tricalcium phosphate (βTCP)) for the upper cartilage and lower bone layer respectively. The 3D printed bi-layered scaffolds with varying infill density, to mimic the native tissue, are not previously explored for OCTE. Hence, we tested the simultaneous osteochondrogenic differentiation inducing potential of the aforesaid 3D printed biphasic scaffolds in vitro, using rabbit adipose derived mesenchymal stem cells (ADMSCs). Further, the biphasic scaffolds were highly cytocompatible, with excellent cell adhesion properties and cellular morphology. Most importantly, these biphasic scaffolds directed the simultaneous differentiation of a single stem cell population in to two cell lineages (simultaneous differentiation of rabbit ADMSCs into chondrocytes and osteoblasts). Further, these scaffolds enhanced the production of ECM and induced robust expression of marker genes that is specific for respective cartilage and bone layers. The 3D printed OCTE scaffold of our study hence can simulate the native osteochondral unit and could be potential futuristic biomimetic scaffold for osteochondral defects. Further in vivo studies are warranted.